PENGARUH KUANTITAS KAPUR TERHADAP KECEPATAN TUMBUH MISELIUM JAMUR TIRAM SEBAGAI UPAYA PEMBUATAN POSTER - Mahsar, Mahsar; Dharmawibawa, Iwan Doddy; Masiah, Masiah (Bioscientist : Jurnal Ilmiah Biologi, 2016)
<!–[if gte mso 9]> <![endif]–><span style="font-size: 10.0pt; line-height: 150%; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; color: #212121; mso-ansi-language: EN-US; mso-fareast-language: IN; mso-bidi-language: AR-SA;">ABSTRACT: <span style="font-size: 10.0pt; line-height: 150%; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: IN; mso-bidi-language: AR-SA;">White oyster mushroom cultivated by the community so that the demand for oyster mushroom growing. White oyster mushroom production in Indonesia is still lacking, it is caused by lack of optimal cultivation of oyster mushroom so it can not meet the public demand for oyster mushroom. This study aims to determine "the influence of the quantity of lime to the oyster mushroom mycelium growing pace as the undertakings posters". The research is a qualitative research experiment arranged in a completely randomized design (CRD), with control PI (lime0%), PII (lime 2%), PIII (lime 4%),respectively <span style="font-size: 10.0pt; line-height: 150%; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; background: white; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">treatment<span style="font-size: 10.0pt; line-height: 150%; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: IN; mso-bidi-language: AR-SA;"> repeated 10 times to obtain 30 baglog trial. The test results showed that treatment of three (PIII) with the provision of limestone (CaCO3) 4% provide optimal results and significant form of speed of growth of mycelium average (PI) 6.3, (PII) 7.2 and (PIII) 7.6 total average is 7.0 , From the results of this research are made in the form of posters. Poster validation results in the field of education. 84.70% with a decent category and language fields gori 87.05% with a decent word. Thus poster made of the results of this research deserves to be used for the community.<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>